Sobre María del Consuelo Maquívar, Sofía Velarde Cruz, Jesús Palomero Páramo, Gabriel Rivera Madrid, Beatriz Sánchez Navarro de Pintado, Natalia Ferreiro Reyes Retana y Rebeca Kraselsky. Escultura: Museo Nacional del Virreinato - Sigaut, Nelly (Historia Mexicana, 2009)
-